1990
DOI: 10.1037/0882-7974.5.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of age-related differences in frequency discrimination with backward masking: Speed of processing or stimulus persistence?

Abstract: In Experiment 1, frequency-discrimination thresholds were estimated in a 2-interval, forced-choice, backward masking procedure with a masker acoustically dissimilar to the targets. Young subjects were more efficient in escaping the effects of masking than were their elderly counterparts. In Experiment 2, young and elderly subjects performed the same task, with a masker acoustically similar to the targets and with a target-dissimilar masker. Under target-similar masking and at short target-masker intervals, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Information theory (Shannon & Weaver, 1949) has been applied to explain age differences in diverse experimental phenomena, such as visual search (Hoyer & Familant, 1987), fragmented pictures identification (Cremer & Zeef, 1987), and auditory stimulus persistence (Raz, Millman, & Moberg, 1990). Increasing processing redundancy may be an optimal way of improving representational signal-to-noise ratio and minimizing transmission errors in a system composed of noisy elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information theory (Shannon & Weaver, 1949) has been applied to explain age differences in diverse experimental phenomena, such as visual search (Hoyer & Familant, 1987), fragmented pictures identification (Cremer & Zeef, 1987), and auditory stimulus persistence (Raz, Millman, & Moberg, 1990). Increasing processing redundancy may be an optimal way of improving representational signal-to-noise ratio and minimizing transmission errors in a system composed of noisy elements.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, age-related deficits in using strategies, deploying attention and encoding contextual cues may all reflect fundamental properties of the aging brain, which has long been viewed as an information processing system with progressively decreasing signal-to-noise ratio (Birren, 1958; Crossman & Szafran, 1956; Layton, 1975; Li, Lindenberger, & Sikström, 2001). Information theory (Shannon & Weaver, 1949) has been applied to explain age differences in diverse experimental phenomena, such as visual search (Hoyer & Familant, 1987), fragmented pictures identification (Cremer & Zeef, 1987), and auditory stimulus persistence (Raz, Millman, & Moberg, 1990). Increasing processing redundancy may be an optimal way of improving representational signal-to-noise ratio and minimizing transmission errors in a system composed of noisy elements.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years several research reports have indicated that elderly listeners may have diminished auditory temporal processing capacity. The evidence for this conclusion comes from different recognition experiments that utilized various forms of temporally degraded speech ͑Harris and Reitz, 1985;Helfer and Wilber, 1990;Gordon-Salant and Fitzgibbons, 1993͒, and other tasks that examined listeners' ability to process the order of sounds presented in a rapid temporal sequence ͑Trainor and Trehub, 1989;Humes and Christopherson, 1991͒. In addition, measures of backward recognition masking suggest that the speed of perceptual processing may be compromised in elderly listeners ͑Newman and Spitzer, 1983;Raz et al, 1990;Phillips et al, 1994͒. By contrast, some basic psychoacoustic estimates of temporal sensitivity measured with simple sounds that involve either the discrimination of amplitude modulation in noise bursts ͑Takahashi and Bacon, 1992͒ or the detection of brief temporal gaps in noise and tone bursts ͑Lutman, 1991; Moore et al, 1992͒ have not always shown consistent deficits in temporal processing among elderly listeners.…”
Section: Introductionmentioning
confidence: 99%
“…There is also auditory evoked-potential research in support of poor gap detection in the elderly (Boettcher et al, 1996). In addition to gap detection, several small-N group studies have demonstrated differences between the performance of young and older adults in various forms of auditory temporal masking (e.g., Zwicker & Schorn, 1982; Newman & Spitzer, 1983; Raz et al, 1990; Cobb et al, 1993; Gehr & Sommers, 1999; Halling & Humes, 2000). Furthermore, recent physiological measurements of auditory forward masking in animals and humans have shown age-related changes in forward masking unrelated to the concomitant effects of peripheral sensorineural hearing loss.…”
mentioning
confidence: 99%